2009
DOI: 10.1002/esp.1814
|View full text |Cite
|
Sign up to set email alerts
|

Average sand particle trajectory examined by the Raindrop Detachment and Wind‐driven Transport (RD‐WDT) process

Abstract: Recent studies of soil loss by the integrated action of raindrop impact and wind transport have demonstrated the significance of this mechanism. This paper presents data obtained during wind-tunnel experiments examining the 'Raindrop Detachment and Wind-driven Transport' (RD-WDT) process to investigate average sand particle trajectory and the spatial extent at which the process operates. In the experimental design, at the same time as the horizontal wind velocities of 6·4, 10, and 12 m s -1 passed through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Geometric mean particle diameter was 250 μm. Calcium carbonate and organic matter contents were 3.3% and 0%, respectively [36]. The traps were placed horizontally on the x-axis and fixed to a mast at the heights of 0.006, 0.08, 0.155, 0.23 and 0.30 m above the tunnel floor measured from the center of the trap's inlet and at x = 6.74 m, i.e., immediately windward from the sand tray as shown in Fig 2.…”
Section: Methodsmentioning
confidence: 99%
“…Geometric mean particle diameter was 250 μm. Calcium carbonate and organic matter contents were 3.3% and 0%, respectively [36]. The traps were placed horizontally on the x-axis and fixed to a mast at the heights of 0.006, 0.08, 0.155, 0.23 and 0.30 m above the tunnel floor measured from the center of the trap's inlet and at x = 6.74 m, i.e., immediately windward from the sand tray as shown in Fig 2.…”
Section: Methodsmentioning
confidence: 99%
“…This process basically opens the floodgates to wider and more complex water erosion processes, in which all detached soil particles and small aggregates are transported further by surface runoff. Depending on the soil, rainfall characteristics, and wind, particles can be displaced by more than 5 m in horizontal distance (Erpul et al, 2009). Other authors have concluded that splash processes also depend on the saturation of the upper soil horizon (Ryzak et al, 2015;Zambon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…(, , , , , ), Erpul et al . (, , ) and Cornelis et al . (, ) (since these are referred to frequently in this paper, a single reference term of ‘ICE WDR studies’ is used in the rest of the manuscript).…”
Section: Introductionmentioning
confidence: 99%
“…For example, works performed in a wind tunnel rainfall simulator at the International Center for Eremology (ICE), Ghent University, Belgium (Gabriels et al, 1997;Cornelis et al, 2004a) on the combined effects of wind and rain had the objectives to understand mechanisms and to develop a process-based erosion model. More information on the wind tunnel studies is given by Erpul (1996Erpul ( , 2001, Erpul et al (1998Erpul et al ( , 2000, Erpul et al (2002Erpul et al ( , 2003aErpul et al ( , 2003bErpul et al ( , 2004aErpul et al ( , 2004bErpul et al ( , 2005, Erpul et al (2008Erpul et al ( , 2009aErpul et al ( , 2009b and Cornelis et al (2004bCornelis et al ( , 2004c) (since these are referred to frequently in this paper, a single reference term of 'ICE WDR studies' is used in the rest of the manuscript). Visser and Cornelis (2004) compiled the papers on 'wind and rain interaction in erosion', and Stroosnijder and Gabriels (2004) highlighted the need for future work on wind and water interaction in erosion models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation